Проектирование и внедрение системы мониторинга обучения - Каипова, С.К (SCIENCE and SOCIETY, 2023)
The article discusses and presents the design and implementation of monitoring in the education system.
Keywords: learning monitoring; implementation; learning process; learning system; design; process quality; effi- ciency; learning quality; educational programs